Schistosoma mansoni antigens alter activation markers and cytokine profile in lymphocytes of patients with asthma - Almeida, Tarcísio Vila Verde Santana de (2017)
Asthma is a chronic disease characterized by airway inflammation, obstruction and hyperresponsiveness. Severe asthma affects a small proportion of subjects but results in most of the morbidity, costs and mortality associated with the disease. Studies have suggested that Schistosoma mansoni infection reduces the severity of asthma and prevent atopy. Objective: We evaluated the ability of S. mansoni antigens, Sm29 and Sm29TSP-2 to modulate lymphocyte activation status in response to the allergen of the mite Dermatophagoides pteronyssinus (Der p1) in cell cultures of individuals with asthma. Methods: Thirty four patients were enrolled in this study: seventeen patients with severe asthma (SA group), seventeen patients with mild asthma (MA group) and six controls with no asthma. Peripheral blood mononuclear cells (PBMC) were obtained and stimulated with Sm29 and Sm29TSP-2 in the presence or absence of Der p1. The expression of surface markers and cytokines on lymphocytes was evaluated by flow cytometry and the levels of IL-10 in the culture supernatant were determined by ELISA. Results: The addition of Sm29 and Sm29TSP-2 antigens to PBMC cultures from both groups of subjects with asthma stimulated with Der p1 reduced the frequency of CD4+CD25low cells whereas and increased frequency of CD4+CD25high population was observed compared to unstimulated cultures. Moreover, cultures stimulated with Sm29TSP-2 showed a reduction in the frequency of T cells expressing CD69, IFN-, TNF and TGF- in the MA group and an increase in the frequency of CD4+TSLPR+ T cells in the SA group. The addition of Sm29 to the cultures reduced the frequency of CD4+CD69+ and CD4+IL-5+ T cells in all asthmatic groups, and reduced the frequency of CD4+ T cells expressing IL-13 in the MA group. The cultures stimulated with Sm29 and Sm29TSP-2 showed an increase in the level of IL-10 in the supernatants. Conclusion: These results suggest that the addition of Sm29 and Sm29TSP-2 to the cells cultures from subjects with asthma reduced cell activation markers and altered the cytokine production pattern in a way that can potentialy control the inflammatory response associated with asthma.